Analisis RPP Mahasiswa Kelas Praktik RPP Pendidikan Agama Kristen - Eirene Mary (Sekolah Tinggi Agama Kristen Samarinda, 2023)
Abstract: One required competence of a teacher is pedagogical competence. A teacher must have the skills to plan a learning program to be able to achieve educational goals. Therefore, student teacher who will become teacher must be educated and trained to be able to prepare learning programs. Lesson Plan Writing Course is one of the required subjects for a student teacher. The student teacher of Christian Education major has enrolled Lesson Plan Writing course and has collected their lesson plans as their final course requirement. This research is conducted to figure out the students’ understanding of the course and their skills in lesson plan writing in accordance to the regulation. The research method is qualitative research that describe the analysis of the students’ lesson plans. The research shows the following: 1) There are varied level of understanding the concept of lesson plan and instructional design. Some students have sufficient understanding, while other students still have poor understanding. (2) Students’ ability in lesson plan writing is fair enough, though there are students who is still lacking. (3) The connection of each component of instructional design should be improved. Abstrak: Salah satu kompetensi yang harus dimiliki oleh seorang guru adalah kompetensi pedagogik. Seorang guru harus memiliki keterampilan untuk merencanakan program pembelajaran untuk dapat mencapai tujuan pendidikan. Dengan demikian para calon guru harus dididik dan dilatih untuk dapat mempersiapkan program pembelajaran. Mata kuliah Praktik RPP menjadi salah satu mata kuliah wajib untuk diikuti oleh mahasiswa calon guru. Mahasiswa program studi pendidikan agama Kristen mengikuti mata kuliah Praktik RPP PAK dan sudah mengumpulkan RPP sebagai tugas akhir. Penelitian ini dibuat untuk melihat sampai sejauh mana pemahaman dan keterampilan para calon guru PAK tersebut dalam membuat rancangan pembelajaran yang sesuai dengan ketentuan yang berlaku. Metode penelitian yang digunakan adalah metode penelitian kualitatif yang menggambarkan hasil analisis dari RPP yang dibuat oleh para mahasiswa. Hasil penelitian menunjukkan bahwa 1) Tingkat pemahaman komponen RPP dan komponen desain pembelajaran para mahasiswa dapat dikategorikan cukup untuk beberapa orang dan cenderung kurang untuk beberapa orang lainnya. (2) Kemampuan mahasiswa terhadap sistematika penyusunan RPP cenderung cukup. Walaupun masih ada 2 orang yang masih kurang dalam hal sistematika penyusunan RPP. (3) Keterkaitan antar komponen dalam desain pembelajaran masih perlu ditingkatkan.